2016
DOI: 10.1080/00958964.2016.1139534
|View full text |Cite
|
Sign up to set email alerts
|

Connection with nature is an oxymoron: A political ecology of “nature-deficit disorder”

Abstract: It has become commonplace to argue that greater "connection with nature" is needed to mobilize support for both biodiversity conservation and environmentalism generally, and hence to call for more effective environmental education to achieve this. I employ a political ecology lens to problematize this increasingly conventional wisdom by highlighting the ways in which a sense of separation from "nature" is in fact paradoxically reinforced by the very environmental education and related practices employed to ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 29 publications
0
69
0
2
Order By: Relevance
“…An aspiration to live more responsibly with others is commonly articulated as a need for greater connection, reversing anti-ecological separatism (Gibson- Graham & Roelvnik, 2009). The field of environmental education has been particularly influenced by the idea that lack of connection with nature is a contemporary malaise to be countered, hence a focus on 'reconnecting children with nature' (Fletcher, 2016). Environmental education programmes operate on the premise that direct experience of the natural world generates knowledge which influences attitudes then enacted in behaviour (Goralnik & Nelson, 2011).…”
Section: Community Gardening As a Route To Environmental Concernmentioning
confidence: 99%
See 2 more Smart Citations
“…An aspiration to live more responsibly with others is commonly articulated as a need for greater connection, reversing anti-ecological separatism (Gibson- Graham & Roelvnik, 2009). The field of environmental education has been particularly influenced by the idea that lack of connection with nature is a contemporary malaise to be countered, hence a focus on 'reconnecting children with nature' (Fletcher, 2016). Environmental education programmes operate on the premise that direct experience of the natural world generates knowledge which influences attitudes then enacted in behaviour (Goralnik & Nelson, 2011).…”
Section: Community Gardening As a Route To Environmental Concernmentioning
confidence: 99%
“…Beyond empirical weaknesses of claims for community gardening as a route to care for nonhumans there are ontological flaws meaning the narrative of reconnection paradoxically, reinforces the notion of human separation from nature (Fletcher, 2016). Much scholarship on urban gardens takes a simplistic view of the relationship between nature and society, assuming a gulf between the two with nature on the positive side of the divide (Classens, 2015).…”
Section: Community Gardening As a Route To Environmental Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes are largely based on emotions, and the strength of an emotional connection toward the natural environment is associated with pro‐environmental behavior (Hinds and Sparks ). In contrast, emotional disconnection hinders conservation (Fletcher ). Although there is disagreement about the direction and strength of links between attitudes and pro‐environmental behaviors (Barthel et al .…”
mentioning
confidence: 99%
“…Through my research I found mindfulness, in a group setting, in the natural world, to be one means of achieving balance, inclusion, and connection (a sense of well-being). While mindfulness opens the possibility of finding connection (Rechtschaffen, 2014), the connection is incomplete if no link is made with the natural world; mindfulness can be a way of forming deeper connections while simultaneously situating the self as one with nature, rather than separate from nature (Fletcher, 2016). "Mindfulness means paying attention in a particular way: on purpose, in the present moment, and non-judgmentally" (Kabat-Zinn, 1994, p. 4).…”
Section: Goals and Objectivesmentioning
confidence: 99%